Group investigation model to improve interpersonal skills - Nur Ainiyah; Anik Ghufron; Marzuki Marzuki; Said Subhan Posangi; Kasim Yahiji; Abdul Rohman; Moch. Tolchah; St. Wardah Hanafie Das (Institute of Advanced Engineering and Science, 2022)
This study aimed to prove the effectiveness of the application of the group investigation learning model in improving students' interpersonal skills. The sample of this study was 116 students, which was determined by a simple random sampling technique. This experimental research used pre-test post-test Control Group Design. Data were obtained by direct observation of the interpersonal skills of students during the learning process. Final observation score of interpersonal skills is 0.026 and the t value count greater than t table (2.272>1.980). Thus, there are differences in interpersonal skills between the experimental class and the control class. This means that the use of the group investigation model is effective in improving students' interpersonal skills.